Optimasi Promosi Digital Kerajinan Tanah Liat dalam Pelestarian Kearifan Lokal Desa Arjawinangun Dengan Pendekatan ABCD - Taufik Ridwan; Nurima Fadilah; Zaenal Arifin; Amaliya amaliya; Aan Ajijah; Inah Inah; Istikanatul Mustafidah; Siti Masitoh; Herdy Ageng Triyatna; Muhamad Nur Arifin; Siti Patimah; Khsusnul Khotimah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The rapid flow of information and this digital era can bring new views in the community related to the promotion of clay crafts to maintain its existence because it is part of the local wisdom of the village. This study aims to describe the existence and popularization in the process of making pottery in Arjawinangun village and how the obstacles faced by pottery craftsmen in the promotion of the digital era with the existence of development steps in clay crafts in Arjawinangun village. The method used is qualitative, data collection techniques with observation and documentation. Data analysis techniques are carried out, namely reducing data, presenting (display) and verification. The results of this study indicate that some people are still producing pottery crafts, crafts produced in the form of rice pots (kanot bu), bellanga (beulangong), rice plates (pinee), cigarette ashtrays and cobek (capah). It is concluded that pottery craftsmen in promotion can use the digital era while the clay craft process in Arjawinangun village goes through several processes, namely: soil processing, pottery formation, pottery drying, and firing process.